Physico-mechanical properties determination using microscale homotopic measurements: Application to sound and caries-affected primary tooth dentin - Marangos, Orestes; Misra, Anil S.; Spencer, Paulette; Bohaty, Brenda S.; Katz, J. Lawrence (My University, 2009)
Microscale elastic moduli, composition and density have rarely been determined at the same location for biological materials. In this paper, we have performed homotopic measurements to determine the physico-mechanical properties of a second primary molar specimen exhibiting sound and caries-affected regions. A microscale acoustic impedance map of a section through this sample was acquired using scanning acoustic microscopy (SAM). Scanning electron microscopy was then used to obtain mineral mass fraction of the same section using backscattered images. Careful calibration of each method was performed to reduce system effects and obtain accurate data. Resorption, demineralization and hypermineralization mechanisms were considered in order to derive relationships between measured mineral mass fraction and material mass density. As a result, microscale mass density was determined at the same lateral resolution and location as the SAM data. The mass density and the acoustic impedance were combined to find the microscale elastic modulus and study the relationship between microscale composition and mechanical properties. © 2008 Acta Materialia Inc.
Keywords: Acoustic microscopy; Density; Dentin; Elastic modulus; Micromechanics